TRADISI MA’NENE (PEMBERSIHAN JENAZAH LELUHUR) PADA MASYARAKAT TORAJA (STUDI KASUS DI DESA TONGA RIU KECAMATAN SESEAN SULOARA’ KABUPATEN TORAJA UTARA) - Kalua?, Windrialde Datu; Tasik, Femmy C. M.; Tumengkol, Selvie M. (HOLISTIK, Journal Of Social and Culture, 2020)
This researchaims to understand more deeply about the tradition of Ma’nene which is a continuation of Aluk Todolo solo’ signs that are transformerd into the Christian version of the Ma’nene tradition, with reference to the focus of research that describes the prosess of implementing the tradition of Ma’nene (cleaning the remains of ancestors) in the Toraja community (case studi in the village of Tonga Riu Sesean Suloara’ district north Toraja regency). This study uses a qualitative method with a descriptive type that emphasizes the description of the object under study based on the facts that eist, determination of informants is done by purposive sampling, namely the determination of informants carried out deliberately with certain criteria that are considered capable of providing information relating to research problems. data collection techniques used in this study are observation and interview techniques in addition, there are also data collection techniques using literature study. The results of this study indicte the process of implementing Ma’nene in a belief almost has in common, but the implementing rules are different, the fuction of the Ma’nene version of Aluk Todolo is to ask for blessing to the spirits of the ancestors, while the function of the Christian version of the Ma’nene for Aluk Todolo and the Christian community has in common the sign of affection and the award of their for families who have died. Keywords: Ma’nene, Tradition, Aluk Todolo, Rambu Solo’